Evaluation of Fire Protection systems in Residential High-rise Buildings for Evacuation Optimisation- A Case of Bengaluru - N, Mamatha.; K, Ajai Chandran. C. (International Journal of Membrane Science and Technology, 2023)
Significance of the research- Among different types of occupancies, a Residential high-rise building presents a more significant challenge to fire protection due to its functionality, complexity, and economic value. Objective of the study- The key objective of the present paper was to examine the situation of physical (as opposed to non-physical) fire protection systems in randomly selected Residential high-rise buildings in Bengaluru for Evacuation optimization. Methodology- Methods used include Physical observation, document review, and interviews. A multi-attribute evaluation model/approach was applied to establish the sufficiency or suitability of fire protection systems in light of NBC-2016 [1] and Bangalore Byelaws-2016. The study reveals that fire-fighting/evacuation lifts and other fire protection systems are primarily present in the buildings. Nevertheless, due to inadequate maintenance or unsuitable elements, their safety performance is compromised. Research findings- The analysis revealed that fire hoses and hydrants demonstrated the highest level of adequacy and suitability in terms of their number, locations, and maintenance across the buildings. Conversely, only 50% of the buildings had a sprinkler system that was sufficiently installed, indicating a need for improved coverage and maintenance, possibly due to cost considerations. The performance of other systems was as follows: fire driveways (83%), fire escape staircases (83%), fire detection and alarm (40%), corridors and passageways (67%), assembly areas (83%), hose reels and hydrants (100%), fire brigade access and facilities (67%), safety signs and notices (17%), portable fire extinguishers (50%), and fire audits (17%). Based on these findings, it is recommended to prioritize increased efforts in inspecting and maintaining fire protection systems throughout the lifespan of the project to address the identified shortcomings. Additionally, the design of residential high-rise buildings should incorporate provisions for fire-fighting evacuation lifts and facilities catering to the needs of disabled individuals.